1967
DOI: 10.1111/j.1469-8986.1967.tb02761.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification in Autonomically Mediated Physiological Responses to Cold Pressor by Cognitive Activity: An Extension

Abstract: The SNS response decrement obtained by Mefferd and Wieland (1965) when a congitive task was imposed during a painful stimulus was reproduced with 15 Ss under conditions involving minimal motor activity. The results support the conclusion that cognitive activity/»er se was the major determinant of the decrement.After a decrease caused by alerting the S for the first passage no further significant changes in BSR occurred. The mean GSR (sum of transient decreases in resistance adjusted to a per minute basis) incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…We first noted in a longitudinal experiment (Mefferd & Wieland, 1965) and confirmed in a cross sectional study (Sadler, Wieland, Mefferd, Benton, & McDaniel, 1967) that when a cognitive task was superimposed at the height of the pain in an ongoing cold pressor exposure, the autonomic activity did not increase as expected. This suggested that although the signals had widely different sources and, supposedly, were processed in different parts of the CNS, the input signals interacted in the CNS so as to reduce or limit the signal fiow to the ANS.…”
supporting
confidence: 62%
“…We first noted in a longitudinal experiment (Mefferd & Wieland, 1965) and confirmed in a cross sectional study (Sadler, Wieland, Mefferd, Benton, & McDaniel, 1967) that when a cognitive task was superimposed at the height of the pain in an ongoing cold pressor exposure, the autonomic activity did not increase as expected. This suggested that although the signals had widely different sources and, supposedly, were processed in different parts of the CNS, the input signals interacted in the CNS so as to reduce or limit the signal fiow to the ANS.…”
supporting
confidence: 62%
“…A common method of assessing pain tolerance or experiences during the administration of pain is the Cold Pressor Test (CPT; Sadler, Welland, Mefferd, et al, 1967; Lovallo, 1975; Stam, Petrusic & Spanos, 1981). In the CPT, the participant immerses one (or both) arms in an ice bath, typically maintained at 1–4 degrees Celsius.…”
Section: Resultsmentioning
confidence: 99%